'I Didn't Know What to Expect': Describing Parents' Expectations in Children's Rehabilitation Services. (3rd May 2020) - Phoenix, Michelle; Smart, Eric; King, Gillian
Abstract: Aims: The aim of this paper is to provide a holistic description of the nature, formation and impact of parents' therapy related expectations. Methods: This qualitative descriptive study drew from initial and follow up interviews with 20 parents of children ≤ 6 years who had a developmental disability or delay and used therapy services at a children's treatment center in Ontario, Canada. Conventional content analysis was used to inductively generate themes and investigator triangulation was completed. Results: Parent's child related expectations focused on whether the child would receive a diagnosis and what they might achieve. Parents held expectations about the availability of service and how it would be offered. Parents' expectations of service providers included their knowledge, skills, relationships and communication with the children and parents. Parents held expectations of themselves related to attendance and roles in therapy sessions and home practice. These expectations are described according to how they are shaped and changed them over time. The impact of matched/mismatched expectations is explored. Conclusion: Service providers can improve family-centred care and collaboration with parents by explicitly discussing parents' expectations when beginning, and throughout, therapy. Parent satisfaction and therapy engagement may improve if parents and service providers negotiate and agree upon expectations.